2011
DOI: 10.1152/ajpregu.00604.2010
|View full text |Cite
|
Sign up to set email alerts
|

AT1 receptors in the paraventricular nucleus mediate the hyperthermia-induced reflex reduction of renal blood flow in rats

Abstract: Increasing body core temperature reflexly decreases renal blood flow (RBF), and the hypothalamic paraventricular nucleus (PVN) plays an essential role in this response. ANG II in the brain is involved in the cardiovascular responses to hyperthermia, and ANG II receptors are highly concentrated in the PVN. The present study investigated whether ANG II in the PVN contributes to the cardiovascular responses elicited by hyperthermia. Rats anesthetized with urethane (1-1.4 g/kg iv) were microinjected bilaterally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Areas in the rostral ventrolateral medulla (RVLM) and in the hypothalamus, (e.g. the paraventricular nucleus (PVN)) have been shown to mediate an increase in sympathetic outflow in response to microinjection of Ang II [15][16][17][18][19][20][21][22][23][24][25]. In studies carried out in rabbits with pacing-induced CHF Liu et al [26] showed that central infusion of the AT1R blocker losartan reduced renal sympathetic nerve activity (RSNA).…”
Section: Central At1r In Heart Failurementioning
confidence: 99%
“…Areas in the rostral ventrolateral medulla (RVLM) and in the hypothalamus, (e.g. the paraventricular nucleus (PVN)) have been shown to mediate an increase in sympathetic outflow in response to microinjection of Ang II [15][16][17][18][19][20][21][22][23][24][25]. In studies carried out in rabbits with pacing-induced CHF Liu et al [26] showed that central infusion of the AT1R blocker losartan reduced renal sympathetic nerve activity (RSNA).…”
Section: Central At1r In Heart Failurementioning
confidence: 99%
“…Nitric oxide and angiotensin II (acts on angiotensin 1A receptor) in the PVN are important in mediating the decrease of mesenteric and renal blood flow during hyperthermia [11, 12]. Sevoflurane does not affect the angiotensin 1A receptor signaling [13].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamic paraventricular nucleus (PVN) seems to play a key role for decrease of the mesenteric and renal blood flow during hyperthermia [ 9 , 10 ]. Nitric oxide and angiotensin II (acts on angiotensin 1A receptor) in the PVN are important in mediating the decrease of mesenteric and renal blood flow during hyperthermia [ 11 , 12 ]. Sevoflurane does not affect the angiotensin 1A receptor signaling [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies found that AT1a is critical for the BP response effects of the brain RAS, whereas the AT1b receptor is involved in the dipsogenic effects of central ANG actions ( Davisson et al, 2000 ). Blockade of AT1a and AT1b receptors with the antagonist losartan in the paraventricular nucleus (PVN) prevents the reflex reduction in renal blood flow induced by elevated core body temperature, underscoring this receptor as a critical mediator of cardiovascular thermoregulatory responses ( Chen et al, 2011 ).…”
Section: The Brain Renin-angiotensin System and The At1a Receptor In Cardiometabolic Controlmentioning
confidence: 99%